Multimodal Cancer Therapy Involving Oncolytic Newcastle Disease Virus, Autologous Immune Cells, and Bi-Specific Antibodies - Schirrmacher, Volker; Fournier, Philippe (Frontiers in Oncology, 2014)
This paper focuses on oncolytic Newcastle disease virus (NDV). This paper summarizes (i) the peculiarities of this virus as an anti-cancer and immune stimulatory agent and (ii) the approaches to further harness this virus as a vector to combat cancer. Special emphasis is given on combining virus therapy with cell therapy and on improving tumor targeting. The review will include some of the authors work on NDV, bi-specific antibodies, and cell therapy as building blocks for a new perspective of multimodal cancer therapy. The broad anti-tumor immune reactivation includes innate and adaptive, tumor antigen (TA) specific and TA independent activities